Spontaneous Rupture of Splenic Hemangioma in a Neonate - Bruno Martinez-Leo; Jorge Vidal-Medina; Jesus Cervantes-Ledezma; Arid Diaz de Leon-Rivera; Edith Diaz-Velasco (EL-Med-Pub, 2016)
Spleen vascular tumors such as hemangiomas, albeit rare, can present during neonatal period with unexplained circulatory shock. We present a case of a newborn with refractory hypovolemic shock and acute abdomen that underwent emergency splenectomy due to spontaneous rupture of a splenic hemangioma.